Impact of attitude towards entrepreneurship education and role models on entrepreneurial intention - Kwaku Amofah; Ramon Saladrigues (Journal of Innovation and Entrepreneurship, 2022)
In this paper, we investigate entrepreneurial intention by applying the Theory of Planned Behaviour (TPB) by Ajzen (1991). We specifically examine the role of gender on entrepreneurial education and role models or parental self-employment (PSE), by carrying out a multi-group analysis (MGA). We used a web-based questionnaire to collect information from 216 students at a Spanish university. Data are analysed with the help of Structural Equation Modelling (SEM)-Partial Least Square (PLS). We conducted a tripartite analysis on Complete, Male, and Female Models. Regarding the Complete and Male Models, all the primary hypotheses (5 in total) were accepted, compared with four for the Female Model. In this study, the primary hypotheses focus on the core variables of the TPB. We recommend the institutionalization of traineeship, elective courses, conference and workshops on entrepreneurship to boost the entrepreneurial spirit of students. Though this study has confirmed the applicability of the TPB model to entrepreneurial intention, we did not find a significant relationship between Males and Females about their entrepreneurial intentions for some relationships. However, this study suggests that the relationship between PSE and perceived behavioural control (PBC) is stronger for Males than Females Our results have implications for entrepreneurship education scholars, program evaluators, and policymakers.
Keywords: 650; Entrepreneurial intention; Parental self-employment (PSE); Students; Theory of Planned Behaviour (TPB)